On the Trail of Foodborne Zoonoses: Bibliometric Map of Salmonellosis Publications in the European Union/European Economic Area Countries - Uyar, Cemile; Alkan, Sevil (The European Research Journal, 2026)
Objectives: Salmonella is the second gastrointestinal infection in the European Union and the European Economic Area (EU/EEA). This study aims to identify the academic publications on salmonellosis in EU/EEA countries. Methods: This study analyses 2,900 articles published in EU/EEA countries between 2000-2025 using Web of Science data. Publications were bibliometrically examined. Results: Germany (1,390 articles) was the leading contributor, followed by France (996 articles). The thematic focus of the studies was antibiotic resistance (34.5%), molecular characterization of Salmonella enterica serotypes (28%) and outbreak epidemiology (22%). The annual number of publications peaked in 2021 with 144 articles. In terms of cooperation, the United Kingdom and Germany were the leaders. Thematic evolution analysis has shown a significant increase in the terms ‘antimicrobial resistance’ and ‘whole genome sequencing’ since 2015. Conclusions: This study showed that research is dominated by antibiotic resistance and molecular characterization studies, with Germany leading the publication output.